Pengaruh Kompensasi terhadap Kinerja Karyawan di PT. Indofood CBP Sukses Makmur tbk Cabang Medan - Kahar Mulyani (Departement of Mathematics Education, 2023)
This study aims to determine whether compensation has a significant effect on employee performance at PT. Indofood CBP Sukses Makmur Tbk Medan Branch and how much influence it has. The method used in this study is a quantitative method with several tests, namely reliability analysis, classical assumption deviation test and linear regression. Based on the results of the primary data regression processed using SPSS 20, the multiple linear regression equation is obtained as follows: Y = 3.374 + 0.259 X1 + 0.802 X2. Partially, the incentive variable (X1) has a significant influence on employee performance. This means that the hypothesis in this study is accepted, as evidenced by the t count > t table (3.366 > 2.006). While the benefits variable (X2) has a significant influence on employee performance. This means that the hypothesis in this study is accepted, as evidenced by the t count > t table (11.658 > 2.006). Simultaneously, incentive variables (X1) and benefits (X2) have a significant influence on employee performance. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (91.321 > 3.17). Incentive variables (X1) and allowances (X2) are able to contribute to the employee commitment variable by 77.5% while the remaining 22.5% is influenced by other variables not examined in this study. From the conclusions above, the authors suggest that the leadership should provide incentives according to the time and conditions so that employees no longer have to wait a long time. Employees should work professionally so that company goals can be in accordance with the desired target.